Transformation of English Vocabulary Learning in Elementary Schools Through Gamification - Nugroho, Heru; Hidayah, Nisrina Ajrina Nur (EXCELLENCE: Journal of English and English Education, 2025)
This study aims to determine teachers' perceptions of the concept of gamification learning models in vocabulary learning in Elementary Schools. Several opinion analyses are discussed in depth, reviewed from the topic of readiness for learning implementation, effectiveness, and its influence in improving vocabulary memorization skills. This type of research is descriptive qualitative with elementary school teachers from a number of schools and different grade levels as subjects. The data collection technique was carried out through interviews, namely by displaying a number of questions in a form that was filled in directly in the form of an opinion description. The results of the study showed that teachers were not yet ready to apply the gamification learning model, because their provisions and foundations in developing new teaching methods were still minimal. Teachers need technical guidance regarding insights into planning and technological innovation. However, teachers believe that the concept of gamification will be effective if applied in teaching English vocabulary. This model is quite interesting, presenting interactive features in it that can form a collaborative learning between peers so as to foster social values, skills and enthusiasm for learning.